Utilization of Social Media for Rural Women Entreprenuer Project: A Case Study of Setiu Wetland - Man, Mustafa; Abu Bakar, Wan Aezwani Wan; Muhamad, Suriyani; Ali, Noraida Hj.; Jalil, Masita@Masila Abd. (International Journal of Engineering and Technology, 2018)
Entrepreneurship empowerment towards rural women remains crucial to attain better living standard among rural communities. To help improve the living livelihood through e- business, the community needs to be equipped with entrepreneurship skill explicitly and Information and Communication (ICT) skill implicitly. This paper presents a study case of rural women entrepreneur in Setiu Wetland, Terengganu, Malaysia under NRGS research grant from the period of 2015 to 2018 by a group of UMT researchers and academicians. The study utilizes facebook social media as the electronic business (e-business) and networking platform in marketing and establishing the local products of Setiu Wetland women entrepreneurs. Through the six (6) months period of tracking the respondent’s income rate, the outcome of this NRGS project depicts 17% of women entrepreneurs achieve linear proportion of increasing income rate, 33% of decreasing income rate and the rest 50% of income shows a fluctuating rate.